Hollow City - Riggs, Ransom; Riggs, Ransom (Philadelphia : Quirk Books, 2014)
Jacob Portman and his newfound friends travel to war-torn 1940 London where they use their unusual talents to find a cure for Miss Peregrine, the beloved headmistress of their orphanage who has been trapped in the body of a bird.
Sequel to: Miss Peregrine's home for peculiar children.
Kirkus Review
Publishers Weekly Annex
School Library Journal
Kirkus Review, January 2014
Library Journal web only, December 2013
Keywords: Orphanages -- Juvenile fiction; Orphanages -- Fiction; Orphanages -- Fiction; London (England) -- Juvenile fiction; London (England) -- Fiction; London (England) -- Fiction; Detective and mystery fiction